BP's pipeline strategy : unlocking the value of Azerbaijan's offshore oil fields - Hutchins, Spencer (SAGE knowledge. Cases., 2016)
In Azerbaijan, observers had hailed it as the 'contract of the century.' In September of 1994, the Azerbaijani government signed a Production Sharing Agreement (PSA) with a consortium of eleven oil companies, collectively known as the Azerbaijan International Oil Company (AIOC). The PSA spelled out the plans to develop a Caspian Sea oil field called Azeri-Chirag-Guneshli (ACG), 37 miles off the shore of Baku, Azerbaijan's capital. The members of the AIOC would invest over $15 billion dollars in this project, making it one of the largest non-military capital investments in the world. For Azerbaijan, the development of ACG promised to transform the economy and reestablish the country as a centre of the oil industry. This case study examines this topic.